Cognitive Strategies, Working Memory, and Growth in Word Problem Solving in Children With Math Difficulties. (July 2015) - Swanson, H. Lee; Lussier, Catherine M.; Orosco, Michael J.
This study investigated the role of strategy instruction and working memory capacity (WMC) on word problem solving accuracy in children with ( n = 100) and without ( n = 92) math difficulties (MD). Within classrooms, children in Grades 2 and 3 were randomly assigned to one of four treatment conditions: verbal-only strategies (e.g., underlining question sentence), verbal + visual strategies, visual-only strategies (e.g., correctly placing numbers in diagrams), or untreated control. Strategy interventions included 20 sessions in both Year 1 and Year 2. The intent-to-treat as well as the "as-treated" analyses showed that treatment effects were significantly moderated by WMC. In general, treatment outcomes were higher when WMC was set to a high rather than low level. When set to a relatively high WMC level, children with MD performed significantly better under visual-only strategy conditions and children without MD performed better under verbal + visual conditions when compared to control conditions.